Características tecnológicas de espécies de pescado com potencial de criação na região sudoeste do Paraná - Nogueira, Barbara Arruda (2016)
The fish meat has a particular chemical composition which gives its high nutritional value. However, this food is identified for being highly perishable and this aspect is often named as a barrier to fish consumption. The southwestern Paraná region, parallel to the country's reality, it is characterized by low fish consumption; and one of the strategies aimed at increasing the consumption of this important protein source is encouraging the production of other species besides tilapia. Within this context, it is necessary to know about the meat characteristics. In this sense, the objective of this study was to evaluate the technological potential of pacu, grass carp and catfish species. To do so, at first, it was discussed the chemical and biometric assessment under two distinct descriptive statistical methods, of the three species; and it was also evaluated the discriminating capacity of the study. In a second moment, an evaluation of effects done by two different processes of washing (acid and alkaline) regarding the removal of nitrogen compounds, pigments and the emulsifying ability of the proteins contained in the protein base obtained. Finally, in the third phase, it was aimed to realize the methodology optimization in GC-MS for the analysis geosmin and MIB (2-metilisoborneol) compounds that are responsible for taste/smell of soil and mold in freshwater fish. The results showed a high protein and low lipid content for the three species. The comparison between means and medians revealed symmetry only for protein values and biometric measurements. Lipids, when evaluated only by the means, overestimate the levels for all species. Correlations between body measurements and fillet yield had low correlation, regardless of the species analyzed, and the best prediction equation relates the total weight and fillet weight. The biometric variables were the best discriminating among the species. The evaluation of the washings, it was found that the acidic and basic processes were equally (p ≥ 0.05) efficient (p ≤ 0.05) for the removal of nitrogen compounds on the fish pulps. Regarding the extraction of pigments, a removal efficiency was recorded only for the pacu species, the data were assessed by the parameters L *, a *, b *. When evaluated by the total color difference (ΔE) before and after washing for both processes (acid/alkaline) the ΔE proved feasible perceived by naked eye for all species. The catfish was characterized as the fish that presents the clearest meat with the basic washing considered the most effective in removing pigments for this species. Protein bases obtained by alkaline washes have higher emulsifying capacity (p ≤ 0.05) when compared to unwashed and washed in acid process pulps. The methodology applied for the quantification of MIB and geosmin, allowed to establish that the method of extraction and purification of analytes had low recovery and future studies should be developed for identification and quantification of MIB and geosmin on fish samples.